Mengungkap Dampak Akuisisi Terhadap Kinerja Keuangan Perusahaan - Pratiwi Putri; I Nyoman Putra Yasa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
Thisi researchi aims to determine the impact of acquisitioni on thei financial performancei of companies through comparative analysis that comparing the financial Iperformance of companies before and after iacquisition. Financial performance here is measured by the liquidity ratios (CR), activity ratios (FATO, TATO), solvency ratios (DER, DAR) and profitability ratios (NPM, ROI, ROE) and market ratio (EPS). This study takes population from all company listed on Indonesian Stock Exchange (IDX) that acquisition activity period of 2014 untill 2015, and obtained a 22 companies. The samples in this study using purposive sampling method, acquired 7 companies. This study used the normality test Shapiro Wilk-Test, Paired Sample T-Test, Wilcoxon's Signed Ranks Test. The results of the hypothesis testing were no significant differences in all financial ratios before and after the acquisition